Fragments of history of KPI mathematics departments - Pekarskas, Vidmantas; Pekarskienė, Aldona (Lietuvos matematikos rinkinys, 2000)
History of Applied and General mathematics departments from foundation of Mathematics department in 1940 till its splitting into two departments in 1962 is analyzed in the article.